Organometallic Manipulations of Fluoroolefins Mediated or Catalyzed by Low-Coordinate Nickel - Sicard, Alexandre (Université d'Ottawa / University of Ottawa, 2016)
Fluoroolefins in general represent a valuable class of feedstock materials which have proven integral to a number of industries including (but not limited to) refrigeration, agrochemicals, pharmaceuticals, and propellants. As ligands for transition metals they are privileged in the relative inertness of the C–F bonds and their electrophilicity, which makes them ideal candidates for coordination chemistry with late, electron rich metals. The scope of this thesis encompasses work with TFE and VDF, two readily available fluoroolefins that are used most commonly in the polymer industry. Through the use of low-coordinate nickel systems, value-added derivatives of these two olefins have been prepared. With TFE, a T-shaped perfluoronickelacyclopentane was obtained upon coordination of the bulky SIPr ligand; this complex underwent hydrogenation to give 1H,4H-octafluorobutane at as low as 5 psi of hydrogen, in addition to giving rise to new ring-opened derivatives and a rare perfluorocyclobutyl complex. In the case of VDF, the regioselective hydrodefluorodimerization to a potentially valuable new refrigerant 2,4,4-trifluorobut-1-ene (HFO-1363pyf) catalyzed by nickel is reported, as well as a dimeric 2,4,4-trifluorobut-1-enylnickel derivative which is proposed in this text to originate from the β-fluoride elimination of an unprecedented 5-membered 2H,2H,4H,4H-tetrafluoronickelacycle.
Keywords: Metallacycle; Nickel; Hydrofluoroolefin; NHC; Phosphine; Tetrafluoroethylene